Examining the Effectiveness and Efficiency of an Innovative Achievement Goal Measurement for Preschoolers - Wu, Chung Chin (Frontiers in Psychology, 2022)
A large number of studies have investigated achievement goals and their related antecedents and consequences above elementary school level. However, few studies have implemented achievement goal assessment to investigate achievement goals and their relevance for preschoolers. No valid measurement has been developed for preschoolers to self-report their achievement goals. The main purposes of this study were twofold: (1) To develop an innovative achievement goal measurement for preschoolers and to investigate the best theoretical model for understanding preschoolers’ achievement goal across gender. (2) To examine the effectiveness and efficiency of the pictorial and pure text measurement format and approaches (for young children’s self-reporting and teachers’ rating purposes, respectively). A total of 364 preschoolers aged 5 years participated in self-report activity, and 32 preschool teachers obtained consent to rate 193 out of 364 preschoolers. Results showed: (1) the developed achievement goal measurement was a valid tool for understanding preschoolers’ achievement goals and was equally suitable for boys and girls. (2) The 6-factor achievement goal model was the best theoretical perspective for understanding preschoolers’ achievement goals across gender. (3) The pictorial measurement format for preschoolers’ self-reporting of achievement goals was a more effective but less efficient way to investigate preschoolers’ achievement goals, while the opposite was the case for the pure text measurement format for teachers’ ratings. Implications for achievement goal literature and future research are discussed.